The Influence of Features, Convenience, and Security on Customer Satisfaction in Bank Sumut Syariah Digital Banking Services Simpang Kayu Besar - Effendi, Lutfiah; Sugianto, Sugianto; Anggraini, Tuti (Pusat P2M Politeknik Negeri Batam, 2024)
The development of information technology has changed the landscape of the banking industry by introducing digital services that facilitate services that are easier, faster and more efficient. Customer satisfaction, which is the main priority for banking, encourages improvements in existing banking services, especially digital services. This study aims to examine the influence of features, convenience, and security of digital banking services on customer satisfaction. The research employs purposive sampling, with the population being customers at Bank Sumut Syariah Simpang Kayu Besar, and the sample size is 85 individuals. Findings from the study indicate that features, convenience, and security partially have a significant positive effect on customer satisfaction. Simultaneous testing demonstrates that features, convenience, and security significantly positively influence customer satisfaction.